Ad Blocking - Gritckevich, Aleksandr; Katona, Zsolt; Sarvary, Miklos (Management Science, 2022)
In recent years, ad blocking has become a significant threat to advertising-supported content. Adblockers typically negotiate with publishers, allowing some ads to go through in return for a payment, a practice called (partial) whitelisting in the industry. Ad blocking has a direct positive effect on consumers by reducing advertising intensity. On the other hand, the practice clearly hurts publishers and reduces their incentives to invest in content quality. Lower content quality, in turn has an indirect negative effect on consumers. This paper builds an analytic model to explore the net impact of ad blocking on consumers, how it depends on various market characteristics, and how uniformly it affects consumers. The results show that under a broad set of market conditions, total consumer surplus and even total welfare decline under ad blocking. Whereas some consumers are always better off with an ad blocker, for the average consumer, the impact of quality decline is larger than that of ad reduction. The analysis highlights the detrimental role of ad blockers’ current revenue model—in which value is created for the consumers but it is captured from publishers—in decreasing quality, consumer surplus, and total welfare. Analyzing the impact of varying levels of negotiation power between the ad blocker and publisher reveals that full negotiation power is not preferred by the ad blocker. A lower negotiation power allows the ad blocker to commit to less value extraction from the publisher, thereby leading to higher content quality. Additional model extensions show that the main results are robust. In the case of multiple publishers with different levels of competition between them, the strong negative effect of ad blocking on quality holds. This paper was accepted by Juanjuan Zhang, marketing.